2012
DOI: 10.1016/j.cell.2011.12.026
|View full text |Cite
|
Sign up to set email alerts
|

A Sterol-Binding Protein Integrates Endosomal Lipid Metabolism with TOR Signaling and Nitrogen Sensing

Abstract: SUMMARY Kes1, and other oxysterol binding protein (OSBP) superfamily members, are involved in membrane and lipid trafficking through trans-Golgi network (TGN) and endosomal systems. We demonstrate that Kes1 represents a sterol-regulated antagonist of TGN/endosomal phosphatidylinositol-4-phosphate signaling. This regulation modulates TOR activation by amino acids, and dampens gene expression driven by Gcn4; the primary transcriptional activator of the general amino acid control regulon. Kes1-mediated repression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 39 publications
6
108
1
Order By: Relevance
“…In yeast, where the type II PI4K homolog Lsb6p is not a major Golgi regulator, the Golgi recruitment of all of the OSH proteins studied were dependent on Pik1p (1783). Moreover, the unique OSBP homolog Kes1p, the deletion of which alleviates the need for the PI transfer protein Sec14p (902), has a complex sterol-regulated antagonistic relationship with TGN/endosomal PtdIns4P signaling (1089). Recent studies have shown that Kes1p (also called Osh4p) exchanges sterols picked up from the ER for PtdIns4P at the Golgi membrane and, hence, the Golgi PtdIns4P made by Pik1p drives Kes1p-mediated sterol transport between the ER and Golgi membranes (339).…”
Section: B Golgimentioning
confidence: 99%
“…In yeast, where the type II PI4K homolog Lsb6p is not a major Golgi regulator, the Golgi recruitment of all of the OSH proteins studied were dependent on Pik1p (1783). Moreover, the unique OSBP homolog Kes1p, the deletion of which alleviates the need for the PI transfer protein Sec14p (902), has a complex sterol-regulated antagonistic relationship with TGN/endosomal PtdIns4P signaling (1089). Recent studies have shown that Kes1p (also called Osh4p) exchanges sterols picked up from the ER for PtdIns4P at the Golgi membrane and, hence, the Golgi PtdIns4P made by Pik1p drives Kes1p-mediated sterol transport between the ER and Golgi membranes (339).…”
Section: B Golgimentioning
confidence: 99%
“…Many physiological processes, including cell migration, angiogenesis, metabolism and development, depend on proper functioning of endocytosis and thus cells have developed multiple mechanisms to ensure proper intracellular trafficking and endocytosis (Fernández-Rojo et al, 2012;Gu et al, 2011;Lee et al, 2014;Mousley et al, 2012;Parachoniak et al, 2011). There are multiple pathways of endocytosis into cells, including, clathrindependent, caveolin-dependent and clathrin-and caveolinindependent internalization.…”
Section: Introductionmentioning
confidence: 99%
“…The elongation process appears to be overdetermined (Mason and Struhl 2005), such that only a few specialized genes require a full complement of cofactors for efficient transcription elongation in vivo (Chavez et al 2001). Whereas the elongation defect described here likely applies broadly to many genes, the impairment of transcription initiation we observed previously in vps mutants (Zhang et al 2008) is restricted to a subset of activators that includes Gcn4, but not Gal4, and seems to involve a signaling pathway that responds to sterol limitation (Mousley et al 2012). Hence, we now interpret the dramatic reductions in expression of Gcn4-dependent lacZ reporters we observed previously in vps15D and vps34D mutants (Zhang et al 2008) to be the compound effect of reduced PIC assembly by Gcn4 and impaired transcription elongation through lacZ CDS.…”
Section: Discussionmentioning
confidence: 70%
“…More recently, evidence was provided that sterol limitation also down-regulates Gcn4 function in the nucleus, in a manner involving sterol binding protein Kes1 and its ability to inhibit PI(4)P-directed vesicular protein trafficking with an attendant increase in cellular sphingolipids. It appears that elevated sphingolipids provoke a reduction in Gcn4 function in a manner involving the CDK8 module of the transcriptional coactivator Mediator complex (Mousley et al 2012).…”
mentioning
confidence: 99%